Analysis of Human Resources Competence in Optimizing the Use of E-Prescriptions in the Outpatient Pharmacy Installation of Datu Kandang Haji Balangan Regional Hospital Year 2024 - Elisabet Ery Novianti; Istiana Kusumastuti (Sean Institute, 2025)
E-prescription is a system that allows doctors to write prescriptions electronically, which can then be accessed by pharmacists and patients through digital devices. The implementation of e-prescription aims to improve the efficiency of health services, accelerate drug access, and improve the accuracy and safety of prescriptions. This study aims to analyze the competence of human resources inthe use of e-prescriptions in the Outpatient Pharmacy Installation of Datu Kandang Haji Balangan Regional Hospital. Method:This research uses qualitative methods.The main informants consisted of specialist doctors and pharmacists, while the triangulation informants consisted of the head of the pharmacy installation, Head of Medical Support Services, Head of Quality and Non-Medical Service Resources and computer administrators.. Collection methodare observation, interviews and documentation. Data analysis includesthe process of organizing, analyzing, and interpreting non-numerical data into concluding information. Research Results:The study showed that human resources in the Outpatient Pharmacy Installation of Datu Kandang Haji Balangan Hospital have a fairly good understanding of work procedures and mastery of e-prescription technology, as well as a positive attitude towards change. Organizational support in the form of policies, training, and communication between staff is also quite optimal. However, there are still obstacles in the technological aspect, such as limited hardware and software, network instability, and lack of features that suit user needs. The lack of technical training also affects the effectiveness of e-prescription use. Increasing technological capacity and ongoing training are the keys to optimizing services. Conclusion: Increasing human resource training, organizational coordination, and strengthening infrastructure and technological features are essential to support more efficient and effective e-prescription use in the Pharmacy Installation of Datu Kandang Haji Balangan Hospital.